Efektivitas Terapi Rendam Kaki Air Hangat untuk Menurunkan Tekanan Darah pada Penderita Hipertensi - Alfath Dzea Haqilana; M. Aqil Argyanto; Satriya Pranata (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Hypertension has become a serious global health issue, with the number of sufferers increasing from 650 million in 1990 to 1.4 billion in 2024. In Indonesia, the prevalence reached 34.1% in 2018, with a higher proportion among women at 36.85%. While pharmacological treatments are available, they often face constraints regarding costs and side effects. Hydrotherapy, specifically warm water foot soaks, serves as a safe and accessible non-pharmacological alternative to lower blood pressure naturally. Objective: This study aims to evaluate the effectiveness of warm water foot soak therapy in reducing blood pressure among hypertension patients. Methods: This study utilized a literature review design by accessing national and international journal databases, including Garuda, ProQuest, and PubMed. The search strategy employed keywords such as "hydrotherapy," "warm water foot soak," and "hypertension". Following the PRISMA method, 13 articles published between 2021 and 2025 were selected based on specific inclusion and exclusion criteria for further analysis. Results: Analysis of the 13 studies consistently showed that warm water foot soak therapy significantly reduces both systolic and diastolic blood pressure (p < 0.05). Meta-analysis results indicated an average reduction of 6-7 mmHg in systolic pressure and 5-6 mmHg in diastolic pressure. The physiological effect is triggered by peripheral vasodilation due to heat exposure, which reduces systemic vascular resistance. The most effective protocol involves water temperatures of 38-40°C for a duration of 15-20 minutes. Conclusion: Warm water foot soak therapy is an effective, economical, and simple non-pharmacological intervention that can be performed independently at home to help transition patients from hypertensive states toward normal blood pressure levels.